Hygrothermal properties of blocks based on eco-aggregates: Experimental and numerical study. (30th October 2016) - Bourdot, Alexandra; Promis, Geoffrey; Tran Le, Anh Dung; Douzane, Omar; Benazzouk, Amar; Rosquoët, Frédéric; Langlet, Thierry
Highlights: The valorisation of eco-aggregates, produced by ACT, in concrete is studied. The carbonated aggregates have thermal performances as lightweight aggregates. The eco-materials allow to reduce heat losses compared to expanded clay. The eco-materials allow to reduce and regulate the relative humidity in a room. These materials can be used as insulating-load-bearing materials in building blocks. Abstract: This paper presents a study of eco-aggregates produced by a new Accelerated Carbonation Technology (ACT) in a sustainable approach. These eco-aggregates, obtained by mixing industrial by-products or wastes such as ashes with carbon dioxide (CO2 ), have some characteristics which make them useful in the field of construction materials such as natural aggregates replacement in concrete or mortar. Hygric and thermal characterizations were performed on carbonated aggregates with adapted methods. The results have been compared to that obtained with two reference aggregates: natural gravel and expanded clay. Then thermal and hygric behaviors of concretes-based on carbonated aggregates were analyzed and discussed in the field of construction. These results proved that carbonated aggregates can be valorized through the manufacturing of concrete building blocks with several advantages: mechanical strength, thermal and hygric inertias. Experimental properties allowed a numerical/digital simulation in dynamic conditions for a simple and multilayered wall using the SPARK object-oriented simulation environment that is adapted to complex problems. Their performances were compared to those of concretes based on two reference aggregates in order to highlight the feasibility of manufacturing building blocks.